Epidemiological characteristics and risk factors of lung adenocarcinoma: A retrospective observational study from North China - Li, Daojuan; Shi, Jin; Dong, Xiaoping; Liang, Di; Jin, Jing; He, Yutong (Frontiers in Oncology, 2022)
Background: The main aim of the study was to research risk factors of lung adenocarcinoma and analyze how the incidence of lung adenocarcinoma varies by time, sex and smoking status in North China. Methods: Lung cancer cases of local household registration that were treated for the first time in the investigating hospital was collected from 11 cities in North China from 2010 to 2017. Baseline characteristics, tumor-related information and information about treatment variables were extracted from the patients' hospital medical record, clinical course records, clinical examinations and clinical imaging studies. Results: 23674 lung cancer cases were collected. Women were at higher risk for lung adenocarcinoma than men. People younger than 65 years old had a higher risk of developing lung adenocarcinoma. People in severely polluted cities were at higher risk for lung adenocarcinoma. Mental workers were more likely to suffer from lung adenocarcinoma than manual workers. Notably, non-smokers were more likely to develop lung adenocarcinoma than smokers. The incidence of lung adenocarcinoma increased significantly in Hebei Province, the incidence of lung small cell carcinoma increased smoothly, but the incidence of lung squamous cell carcinoma decreased during 2010-2017. Among non-smokers, the incidence of lung adenocarcinoma and small cell carcinoma showed a higher rise than that in smokers. Conclusions: Lung adenocarcinoma is the most common histological types of lung cancer in North China (Hebei Province), and the incidence of lung adenocarcinoma and lung small-cell carcinoma is increasing, especially among non-smokers. Lung adenocarcinoma is more common in women, under 65 years old, severely polluted cities, non-smokers.